Effectiveness of Mathematics Modules Based on Problem-Based Learning to Improve Students Reasoning Ability in Junior High School - Lestari, Puji; Mardiyana, Mardiyana; Slamet, Isnandar (UIII Press, 2022)
This study aims to determine the effectiveness of mathematics modules based on problem-based learning to improve the reasoning ability of eighth grade students at Junior High School (SMPN) 2 Jumapolo. Reasoning ability is one of the goals of mathematics education, the problem is that the reasoning ability of eighth grade students in Indonesia, including at SMPN 2 Jumapolo, is still relatively low. The development of mathematics modules based on problem-based learning is expected to be a solution to overcome these problems. In this study, the mathematics module based on problem-based learning was tested on thirty eighth grade students at SMPN 2 Jumapolo. This research is quasi-experimental research with One Group Pretest Posttest Design. Samples were taken by cluster random sampling. Students are given a pretest to determine the students’ initial reasoning ability. The students were given treatment in the form of learning by using a mathematics module based on problem-based learning. After that, students were given a post-test to measure the students’ final reasoning ability. The data collection technique used in this study was a test of reasoning ability. The data analysis technique used was the paired t-test. Based on the results of the paired t-test, it was found that the students’ final reasoning ability was better than students’ initial reasoning ability. The students’ reasoning ability increased by 52.80 percent. This shows that the mathematics module based on problem-based learning was effective in improving the reasoning ability of grade eight students.